2014
DOI: 10.1155/2014/246476
|View full text |Cite
|
Sign up to set email alerts
|

Two Congenital Anomalies in One: An Ectopic Gallbladder with Phrygian Cap Deformity

Abstract: The gallbladder is affected by a large number of congenital anomalies, which may affect its location, number, size, or form. Some of these malformations are very rare and may lead to misdiagnosis. An ectopic gallbladder can be misinterpreted as agenesis of the organ or as a cystic hepatic mass when intrahepatic. Given the frequency and the wide acceptance of the ultrasonographic examination of the biliary tract, radiologists should be aware of these malformations. In some cases, ultrasonographic diagnosis can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…Some of gallbladder malformations are very rare and may lead to misdiagnosis. Being difficult to diagnose during routine preoperative studies, these anomalies can provide surgeons with an unusual surprise during laparoscopic surgery [31][32][33].…”
Section: Eus and Gallbladder Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of gallbladder malformations are very rare and may lead to misdiagnosis. Being difficult to diagnose during routine preoperative studies, these anomalies can provide surgeons with an unusual surprise during laparoscopic surgery [31][32][33].…”
Section: Eus and Gallbladder Anomaliesmentioning
confidence: 99%
“…Studies have shown that intraoperative ultrasound and postoperative MRCP or EUS can help in the diagnosis of agenesis or ectopic gallbladder. Overall, it is thought that ultrasonography is the primary imaging modality for gallbladder anomalies with CT, MRI being even more helpful, and the MRCP or EUS providing a more thorough visualization of the biliary tract [31,34,35].…”
Section: Eus and Gallbladder Anomaliesmentioning
confidence: 99%
“…All these variations should be kept in mind during ultrasonographic examination with no visualization of the gallbladder so that misdiagnosis of agenesis is prevented. 1 A left-sided gallbladder is a rare congenital anomaly defined as a gallbladder attached to the lower surface of the left lateral segment of the liver. The gallbladder is located under the left lobe of the liver between segments III and IV or on segment III to the left of the round ligament.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This abnormality was first described by Boyden in 1935, [2][3][4][5] and its estimated incidence is 4%. [2][3][4] This developmental defect appears as folded gallbladder and results from kinking between the body and the fundus or the infundibulum. These deformities predispose to cholelithiasis due to biliary stasis in the corpus and fundus of the gallbladder.…”
Section: Introductionmentioning
confidence: 99%
“…These deformities predispose to cholelithiasis due to biliary stasis in the corpus and fundus of the gallbladder. 1 Phrygian cap anomaly by itself does not suggest invasive intervention, [2][3][4] but the suspicion of associated gallbladder polypsmay indicate the needfor surgical management. [7][8][9] The malignant potential of 10 mm polyps is high, but the smallerones must also be monitored.…”
Section: Introductionmentioning
confidence: 99%